Kompetensi Guru dalam Pemanfaatan Media Pembelajaran untuk Menumbuhkan Minat Belajar Siswa pada Mata Pelajaran SKI di MI - Munawwir Munawwir; Martha Intan Sari; Arini Fitri Oktavia (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2026)
This research stems from the issue of Islamic Cultural History (SKI) lessons often being perceived as boring and unoriginal. The study aims to examine teacher competence in using digital media, how it sparks student interest, and find solutions to existing challenges. Using a descriptive qualitative method, this study offers a fresh perspective for future educators in presenting historical material. The results show that teachers' technological mastery significantly influences the presentation of engaging and non-monotonous content. Proper use of digital media is proven to make students more enthusiastic about the subject. Although there are obstacles like limited facilities and technical skills, these can be overcome through teacher creativity in using free applications and self-training. These findings emphasize the importance of technological adaptation for SKI teachers in the modern era.